The Application of Legal Certainty on Electronic Certificates in Indonesian Agrarian Law - Lingga, Firdo (Jurnal Daulat Hukum, 2023)
In fact, often these physical land certificates are easily duplicated. This of course makes the owner of the land certificate suffer losses. This research aims to examine and analyze legal certainty for electronic land certificates as proof of ownership of land rights in Indonesia; and to review and analyze the legal protection of data on electronic land certificate ownership rights. The approach method used in this study is a normative legal approach. The results of the study show that: (1) Legal certainty of land certificates in the form of electronic documents can be categorized as electronic evidence which has the same evidentiary power as written/written evidence made on paper and the printout as a form of valid proof. (2) Legal protection that can be given to electronic land certificate ownership data consists of: a) Preventive legal protection in the form of guaranteed fulfillment of personal data protection by requiring Electronic System Operators in this case the National Land Agency (BPN) to maintain the confidentiality of public personal data and safeguard it so that there is no leakage.